Lithium iron phosphate material and preparation method thereof, positive pole piece and lithium ion battery

Through the combination of airflow crushing and nano-treating treatment, the problem of difficult to control the particle ratio of lithium iron phosphate materials in traditional methods is solved, and the preparation of lithium iron phosphate materials with high compaction density is achieved, which simplifies the process and improves the material performance. and production controllability.

CN119191251APending Publication Date: 2024-12-27GUANGDONG GUANGHUA SCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411330238.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional methods are difficult to control the ratio of particles of lithium iron phosphate material, and the steps are complicated and complicated, which is not conducive to mass production of high-pressure density lithium iron phosphate materials.

Method used

By preparing a mixture containing iron, phosphorus, lithium, carbon source and dopants, gas-flow crushing and nano-treating treatment, combined with drying and sintering treatment, one-step calcination method is used to utilize the differences in particle size and reactivity. The precursor is blended to obtain a high-pressure lithium iron phosphate material with a large and small particle grading effect.

Benefits of technology

The preparation of high-pressure density lithium iron phosphate material is realized, the process is simplified, the controllability and stability of mass production is improved, and the energy density and rate performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191251A_ABST
    Figure CN119191251A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a lithium iron phosphate material and a preparation method thereof, a positive pole piece and a lithium ion battery. The preparation method of the lithium iron phosphate material comprises the following steps: preparing a mixture containing an iron source, a phosphorus source, a lithium source, a carbon source and a doping agent, performing first airflow crushing treatment on part of the mixture to obtain a precursor A, and recording the rest of the mixture as a precursor B; mixing the precursor A, the precursor B and a solvent, and performing nanocrystallization treatment to obtain slurry; and carrying out drying treatment, second airflow crushing treatment and sintering treatment on the slurry to obtain the lithium iron phosphate material. According to the preparation method, two precursors with obvious difference in particle size and reaction activity are mixed, and nanocrystallization, drying, secondary airflow crushing treatment and sintering treatment are performed, so that the high-compaction lithium iron phosphate material with a large and small particle grading effect is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a lithium iron phosphate material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in 3C products, energy storage systems and power batteries due to their high energy density, long cycle life, good rate performance and low cost. How to further improve the energy density and cycle life of lithium-ion batteries has also become a research hotspot in the field of lithium-ion batteries. As the core part of lithium-ion batteries, positive electrode materials play a vital role in the preparation of high-performance lithium-ion batteries.

[0003] Lithium iron phosphate materials are widely used in new energy vehicles such as electric vehicles (EVs) and hybrid electric vehicles (HEVs) due to their high safety, long cycle life, relatively low cost and good thermal stability. However, the energy density of the battery system composed of them is relatively low, which limits their application in power batteries. The energy density of lithium iron phosphate materials is not only related to capacity, but also closely related to compaction density. However, traditional methods make it difficult to control the ratio of large and small particles of lithium iron phosphate materials, and the steps are cumbersome and complicated, which is not conducive to mass production of lithium iron phosphate materials with high compaction density. Summary of the invention

[0004] Based on this, it is necessary to provide a lithium iron phosphate material and its preparation method, a positive electrode plate and a lithium-ion battery to solve the problem that traditional methods are difficult to control the ratio of large and small particles of lithium iron phosphate materials, and the steps are cumbersome and complicated, which is not conducive to mass production of lithium iron phosphate materials with high compaction density.

[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:

[0006] In a first aspect of the present application, a method for preparing a lithium iron phosphate material is provided, comprising the following steps:

[0007] A mixture containing an iron source, a phosphorus source, a lithium source, a carbon source and a dopant is prepared, and a part of the mixture is subjected to a first airflow pulverization treatment to obtain a precursor A, and the remaining mixture is recorded as a precursor B;

[0008] The precursor A, the precursor B and a solvent are mixed and nano-processed to obtain a slurry;

[0009] The slurry is subjected to a drying process, a second air flow pulverization process and a sintering process to obtain the lithium iron phosphate material.

[0010] In one embodiment, the mass ratio of the precursor A to the precursor B is (1~9):(1~9).

[0011] In one embodiment, the D50 particle size of the precursor A is 1 μm to 2 μm, and the D50 particle size of the precursor B is 8 μm to 10 μm.

[0012] In one embodiment, the molar ratio of the iron element in the iron source, the phosphorus element in the phosphorus source and the lithium element in the lithium source is 1:(0.95~1.05):(1.01~1.05).

[0013] In one embodiment, the iron source includes one or more of ferric phosphate, ferric nitrate, ferric sulfate, ferric chloride, ferrous oxalate, ferrous acetate, ferrous sulfate, ferrous chloride and ferrous oxide;

[0014] In one embodiment, the phosphorus source includes one or more of ferric phosphate, phosphoric acid, dihydrogen phosphate and monohydrogen phosphate;

[0015] In one embodiment, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium chloride, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium oxalate and lithium acetate;

[0016] In one embodiment, the molar ratio of the carbon element in the carbon source, the doping element in the dopant, and the iron element in the iron source is (7-10):(0-1.16):100;

[0017] In one embodiment, the carbon source comprises one or more of glucose, sucrose, fructose, starch, cellulose, citric acid, polyethylene glycol and polyvinyl alcohol;

[0018] In one embodiment, the doping element in the dopant includes one or more of titanium, magnesium, aluminum, vanadium, niobium, zirconium, lanthanum and yttrium.

[0019] In one embodiment, the drying process comprises spray drying;

[0020] The inlet air temperature of the spray drying process is 230°C to 260°C, and the outlet air temperature is 95°C to 120°C.

[0021] In one embodiment, the sintering process comprises the following steps:

[0022] In a protective atmosphere, raise the temperature to 800℃~900℃ and keep it warm for 5h~8h.

[0023] In a second aspect of the present application, a lithium iron phosphate material is provided, which is prepared by the preparation method of the lithium iron phosphate material as described above.

[0024] In one embodiment, the carbon content of the lithium iron phosphate material is 1.20% to 1.30%;

[0025] In one embodiment, the compaction density of the lithium iron phosphate material is ≥2.47 g / cm 3 ;

[0026] In one of the embodiments, the 1C / 0.1C ratio of the lithium iron phosphate material is ≥86.16%.

[0027] In a third aspect of the present application, a positive electrode plate is provided, comprising the lithium iron phosphate material as described above.

[0028] In a fourth aspect of the present application, a lithium-ion battery is provided, comprising the positive electrode plate as described above.

[0029] This application has at least the following beneficial effects:

[0030] The present application performs a first airflow crushing treatment on part of the mixture, thereby obtaining a precursor A with refined particles and more reactive sites, which is beneficial to promoting the growth of lithium iron phosphate grains. The remaining mixture is used as precursor B, which has not undergone any crushing treatment, so the particles are larger, the reactive sites are fewer, and the growth rate of lithium iron phosphate grains is slower. Two precursors with obvious differences in particle size and reactivity are blended, and nano-sized, dried, second airflow crushing and sintering are performed to obtain a high-density lithium iron phosphate material with a large and small particle grading effect. At the same time, the present application adopts a one-step calcination method, which does not require the introduction of materials of different particle sizes during the grinding or mixing of finished materials, does not require the use of cumbersome and complicated processes such as batch feeding, multi-stage sintering and long-term heat preservation sintering, and the synthesis process is simple and controllable, and the stability between batches is good, which is conducive to the mass production of high-density lithium iron phosphate materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0032] Figure 1 is a schematic flow chart of a method for preparing a lithium iron phosphate material in an embodiment;

[0033] Figure 2 This is a SEM image of the lithium iron phosphate material of Example 1;

[0034] Figure 3 is a SEM image of the lithium iron phosphate material of Example 2;

[0035] Figure 4This is a SEM image of the lithium iron phosphate material of Example 3;

[0036] Figure 5 This is the SEM image of the lithium iron phosphate material of Comparative Example 1. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0039] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0040] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0041] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0042] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0043] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0044] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.

[0045] the term

[0046] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0047] Particle size: For spherical particles, particle size refers to the diameter of the spherical particles. For non-spherical particles, particle size usually refers to the equivalent particle size of the non-spherical particles (generally referred to as particle size). The particle size measured by a laser particle size analyzer is the equivalent diameter of the particle. Among them, the equivalent particle size means that when a certain physical property of a particle is the same or similar to that of a homogeneous spherical particle, the diameter of the spherical particle is used to represent the diameter of the actual particle. Unless otherwise specified or there is a contradiction, the particle size in this application represents the equivalent particle size.

[0048] Particle size distribution parameters: In the particle size distribution curve of particles, the particle size corresponding to the cumulative particle size distribution percentage reaching N% is called the DN particle size, which means that the particles smaller than this particle size account for N% of all particles, where N=0~100. When N=100, the D100 particle size indicates the particle size corresponding to the cumulative particle size distribution percentage reaching 100%. When N=50, the D50 particle size is the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, indicating the median particle size or median diameter, indicating that particles smaller than and larger than this particle size each account for 50%. For example, D50 particle size = 1mm, which means that particles smaller than 1mm and particles larger than 1mm each account for 50% of all particles.

[0049] Compaction density: refers to the ratio of the surface density and thickness of the material, in g / cm 3 Generally speaking, the energy density of positive electrode materials applied to lithium-ion batteries is not only related to the capacity, but also closely related to the compaction density of the material. For positive electrode materials with the same capacity, the greater the compaction density, the higher the volume energy density of the battery. Therefore, compaction density is also considered to be one of the important reference indicators of material energy density.

[0050] The energy density of the battery system composed of lithium iron phosphate materials is relatively low, which limits its application in power batteries. At present, the capacity of commercially available lithium iron phosphate materials is close to its theoretical value, and there is little room for improvement. Therefore, it is necessary to increase the compaction density of lithium iron phosphate materials to improve their energy density. To prepare lithium iron phosphate materials with high compaction density, it is usually necessary to use lithium iron phosphate materials with larger particle sizes and lithium iron phosphate materials with smaller particle sizes for particle grading.

[0051] There are three main methods to improve the compaction density of lithium iron phosphate: (1) Introducing different types of iron sources from the raw materials. Due to the different reaction temperatures of different iron sources, lithium iron phosphate with large and small particle grading effect can be prepared; (2) Introducing materials of different particle sizes during the grinding process, finished product mixing and other processes, so that the lithium iron phosphate finished product has the effect of large and small particle grading effect; (3) By regulating the sintering temperature of lithium iron phosphate, through methods such as temperature increase sintering and staged sintering, the growth rate of lithium iron phosphate particles is different, forming the effect of large and small particle grading and improving the compaction density.

[0052] It has been reported that the iron source, lithium source, phosphorus source, carbon source and dopant are added to the grinder in batches, and continuous grinding is used to achieve the gradation of large and small particles of the slurry, thereby producing a lithium iron phosphate material with a high compaction density. This method cannot accurately control the ratio of large and small particles. At the same time, the process of adding raw materials in batches and continuous grinding is cumbersome and complicated. Different raw materials will cause obvious differences in grinding efficiency, which is not conducive to mass production.

[0053] It has been reported that the sintering process is two-stage, with the first stage sintering at a lower temperature to ensure the integrity of the lithium iron phosphate crystal form, and the second stage sintering at a higher temperature to promote the growth of lithium iron phosphate grains, thereby increasing the compaction density. However, the sintering process of this method is relatively complicated, the sintering time is long, and it is not conducive to the large-scale production of high-density lithium iron phosphate materials.

[0054] It can be seen that the traditional method of using materials of different particle sizes to mix or multi-stage sintering to improve the compaction density of lithium iron phosphate materials is not only difficult to accurately control the ratio of large and small particles, which easily leads to poor grading of large and small particles, which is not conducive to improving the compaction density, but also the process is cumbersome and complicated and is not suitable for mass production.

[0055] Based on this, in the first aspect of the present application, a method for preparing a lithium iron phosphate material is provided to solve the problem that the traditional method is difficult to control the ratio of large and small particles of the lithium iron phosphate material, and the steps are cumbersome and complicated, which is not conducive to the mass production of lithium iron phosphate materials with high compaction density.

[0056] See also Figure 1 , which is a schematic diagram of a process for preparing a lithium iron phosphate material in an embodiment. Figure 1 As shown, the preparation method of lithium iron phosphate material includes the following steps:

[0057] S100: preparing a mixture containing an iron source, a phosphorus source, a lithium source, a carbon source and a dopant, performing a first airflow pulverization process on a portion of the mixture to obtain a precursor A, and the remaining mixture is recorded as a precursor B;

[0058] S200: Precursor A, precursor B and solvent are mixed and nano-processed to obtain slurry;

[0059] S300: performing drying treatment, second air flow pulverization treatment and sintering treatment on the slurry to obtain lithium iron phosphate material.

[0060] The present application performs a first airflow crushing treatment on part of the mixture, thereby obtaining a precursor A with refined particles and more reactive sites, which is beneficial to promoting the growth of lithium iron phosphate grains. The remaining mixture is used as precursor B, which has not undergone any crushing treatment, so the particles are larger, the reactive sites are fewer, and the growth rate of lithium iron phosphate grains is slower. Two precursors with obvious differences in particle size and reactivity are blended, and nano-sized, dried, second airflow crushing and sintering are performed to obtain a high-density lithium iron phosphate material with a large and small particle grading effect. At the same time, the present application adopts a one-step calcination method, which does not require the introduction of materials of different particle sizes during the grinding or mixing of finished materials, does not require the use of cumbersome and complicated processes such as batch feeding, multi-stage sintering and long-term heat preservation sintering, and the synthesis process is simple and controllable, and the stability between batches is good, which is conducive to the mass production of high-density lithium iron phosphate materials.

[0061] The following is a detailed description of the preparation method of lithium iron phosphate material in a step-by-step manner.

[0062] S100: preparing a mixture containing an iron source, a phosphorus source, a lithium source, a carbon source and a dopant, subjecting part of the mixture to a first airflow pulverization treatment to obtain a precursor A, and the remaining mixture is recorded as a precursor B.

[0063] Traditional mechanical pulverization methods can usually only pulverize to a particle size range of tens of microns or even coarser. During the pulverization process, it will directly contact with mechanical parts, which will affect the purity of the product and may cause the properties of heat-sensitive, easily oxidized or mechanically sensitive materials to change or be destroyed. Airflow pulverization is a process that uses high-speed airflow (such as compressed air or superheated steam) to drive material particles to collide and rub against each other and against the container wall to achieve pulverization. The high-speed airflow makes the material particles obtain extremely high speeds, and produces huge impact force in the instantaneous collision, thereby crushing the material into fine particles. Compared with traditional mechanical pulverization methods, airflow pulverization can make the material obtain very fine particle size, even reaching nanometer-level particle size; there is no direct contact with mechanical parts during the pulverization process, which can avoid the introduction of impurities, so the product purity is high; less heat is generated during the pulverization process, and the pulverization time is short, which can minimize side reactions such as thermal decomposition and oxidation. It is particularly suitable for the pulverization of heat-sensitive, low-melting-point and easily oxidized materials.

[0064] The mechanochemical activation in the airflow milling process will not only cause physical changes such as crushing and refinement of the material, but also cause a series of changes in the crystal structure, surface morphology, surface chemical composition and surface charge distribution of the particles, resulting in the appearance of a large number of fresh surfaces and highly chemically active sites, thereby enhancing the chemical activity of the particle surface and promoting the growth of lithium iron phosphate grains. At the same time, the high turbulence brought by the high-speed airflow will cause violent collisions and frictions between the particles, so that the different components in the material are fully in contact, the binding energy is transferred, and it has a certain surface modification effect.

[0065] Therefore, the present application utilizes airflow pulverization to adjust the reactivity of the precursor material, and promotes precursors with different reactivity to form lithium iron phosphate grains of different particle sizes to achieve the effect of large and small particle grading. Among them, precursor A is subjected to the first airflow pulverization treatment, which improves the dispersion uniformity and grinding efficiency, and has a mechanochemical activation effect, so that the particles are refined, the specific surface area is increased, the surface energy is increased, and a large number of reactive sites are generated, so it has a higher chemical reactivity. Precursor B has not undergone any pulverization treatment, and its dispersibility, grinding efficiency and chemical reactivity are relatively low. Precursor A and precursor B are mixed in a certain proportion. Thanks to the difference in the chemical reactivity of the two precursors, the growth rate of the lithium iron phosphate grains also produces a significant difference, thereby obtaining a high-density lithium iron phosphate material with a large and small particle grading effect.

[0066] Optionally, the mass ratio of precursor A to precursor B is (1-9): (1-9). As an example, the mass ratio of precursor A to precursor B can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 2:1, 2:3, 2:5, 2:9, 3:1, 3:2, 3:4, 3:5, 3:8, 4:1, 4:3, 4:5, 4:9, 5:1, 5:2, 5:6, 5:9, 6:1, 6:5, 6:7, 7:1, 7:5, 7:8, 8:1, 8:5, 8:9, 9:1, 9:5 or 9:8. Further optionally, the mass ratio of precursor A to precursor B is (2-8): (2-8), for example 2:8, 5:5 or 8:2.

[0067] In the present application, by controlling the mass ratio of precursor A and precursor B, the ratio of large and small particles can be precisely controlled, thereby effectively improving the compaction density of lithium iron phosphate.

[0068] Optionally, the D50 particle size of the precursor A is 1 μm to 2 μm. As an example, the D50 particle size of the precursor A may be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm.

[0069] Optionally, the D50 particle size of the precursor B is 8 μm to 10 μm. As an example, the D50 particle size of the precursor B may be 8 μm, 8.2 μm, 8.4 μm, 8.5 μm, 8.6 μm, 8.8 μm, 9 μm, 9.2 μm, 9.4 μm, 9.5 μm, 9.6 μm, 9.8 μm or 10 μm.

[0070] Optionally, the molar ratio of the iron element in the iron source, the phosphorus element in the phosphorus source, and the lithium element in the lithium source is 1:(0.95-1.05):(1.01-1.05). As an example, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source can be 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99, 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04 or 1:1.05, and can be further selected as 1:1; the molar ratio of the iron element in the iron source to the lithium element in the lithium source can be 1:1.01, 1:1.02, 1:1.03, 1:1.04 or 1:1.05, and can be further selected as 1:1.02.

[0071] Optionally, the iron source includes one or more of ferric phosphate, ferric nitrate, ferric sulfate, ferric chloride, ferrous oxalate, ferrous acetate, ferrous sulfate, ferrous chloride and ferrous oxide, and may further be ferric phosphate.

[0072] Optionally, the phosphorus source includes one or more of ferric phosphate, phosphoric acid, dihydrogen phosphate and monohydrogen phosphate. Among them, the dihydrogen phosphate can be ammonium dihydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate or lithium dihydrogen phosphate, and the monohydrogen phosphate can be diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate or dilithium hydrogen phosphate. Further optionally, the phosphorus source is ferric phosphate.

[0073] Optionally, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium chloride, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium oxalate and lithium acetate, and may further be lithium carbonate.

[0074] Optionally, the molar ratio of the carbon element in the carbon source, the doping element in the dopant and the iron element in the iron source is (7-10):(0-1.16):100. As an example, the molar ratio of the carbon element in the carbon source to the iron element in the iron source can be 7:100, 7.2:100, 7.5:100, 7.8:100, 8:100, 8.2:100, 8.5:100, 8.8:100, 9:100, 9.2:100, 9.5:100, 9.8:100 or 10:100; the molar ratio of the doping element in the dopant and the iron element in the iron source can be is 0:100, 0.01:100, 0.05:100, 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1:100, 1.02:100, 1.05:100, 1.08:100, 1.1:100 or 1.16:100.

[0075] Optionally, the carbon source includes one or more of glucose, sucrose, fructose, starch, cellulose, citric acid, polyethylene glycol (PEG) and polyvinyl alcohol (PVA), and can further be one or more of glucose, citric acid, polyethylene glycol and polyvinyl alcohol, such as a combination of glucose and citric acid, a combination of glucose and PEG, a combination of glucose and PVA, etc. Wherein, the molecular weight of PEG and PVA is 100-10000, such as 100, 200, 400, 600, 800, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000.

[0076] In the present application, by introducing a suitable carbon source, a carbon coating treatment can be achieved to improve the electronic conductivity of the lithium iron phosphate material, thereby improving the specific capacity and rate performance of the lithium iron phosphate material.

[0077] Optionally, the doping element in the dopant includes one or more of titanium, magnesium, aluminum, vanadium, niobium, zirconium, lanthanum and yttrium, and may further be titanium.

[0078] In the present application, the specific capacity of the lithium iron phosphate material can be improved by introducing suitable doping elements.

[0079] Optionally, the dopant includes one or more of oxides, chlorides, hydroxides, inorganic salt compounds and metal organic compounds containing doping elements, including but not limited to: titanium dioxide, carbon tetrachloride, titanium sulfate, titanium nitrate, tetrabutyl titanate, isopropyl titanate; magnesium oxide, magnesium chloride, magnesium hydroxide, magnesium nitrate, magnesium sulfate, magnesium carbonate; aluminum oxide, aluminum chloride, aluminum hydroxide, aluminum nitrate, aluminum sulfate and aluminum carbonate; vanadium pentoxide, ammonium metavanadate; niobium pentoxide, niobium chloride, niobium sulfate, niobium ethoxide; zirconium oxide, zirconium chloride, zirconium sulfate, zirconium nitrate; lanthanum oxide, lanthanum chloride, lanthanum sulfate; yttrium oxide, yttrium chloride, yttrium sulfate. Further optionally, the dopant is titanium dioxide.

[0080] It can be understood that among the above-mentioned iron source, phosphorus source, lithium source, carbon source and dopant, the raw materials used can be compounds that do not contain bound water, such as anhydrous iron phosphate, anhydrous lithium carbonate, anhydrous glucose, etc., or can be compounds that contain bound water, such as dihydrated iron phosphate, monohydrated lithium hydroxide, monohydrated glucose, etc.

[0081] S200: Precursor A, precursor B and a solvent are mixed and nano-processed to obtain a slurry.

[0082] In the present application, the precursor A and the precursor B can be fully mixed through nano-processing, and the particle size can be controlled within a narrower distribution range, and the slurry consistency is good.

[0083] Optionally, the solid content of the mixture obtained by mixing precursor A, precursor B and solvent is 30% to 50%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%, and can further be 40%.

[0084] Optionally, the solvent includes water and an organic solvent, the water may be tap water, distilled water, reverse osmosis water, deionized water, pure water or ultrapure water, and the organic solvent may be ethanol.

[0085] Optionally, the nano-processing includes one or more of sand milling and ball milling, and further can be sand milling. The size of the grinding balls used in the sand milling is smaller than that of the grinding balls used in the ball milling, which is conducive to obtaining a slurry with finer particle size and better dispersibility. Specifically, the grinding balls used in the sand milling include zirconium oxide ceramic balls (abbreviated as zirconium balls), and the particle size of the zirconium balls is 0.3 mm to 0.6 mm.

[0086] Optionally, the D50 particle size of the slurry is 500 nm to 900 nm, for example, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm or 900 nm.

[0087] S300: performing drying treatment, second air flow pulverization treatment and sintering treatment on the slurry to obtain lithium iron phosphate material.

[0088] Optionally, the slurry is subjected to drying treatment, a second airflow pulverization treatment and a sintering treatment, comprising the following steps: drying the slurry to obtain a dried material; subjecting the dried material to a second airflow pulverization treatment to obtain a crushed material; and sintering the crushed material to obtain a lithium iron phosphate material.

[0089] Optionally, the drying process includes spray drying, which may further be centrifugal spray drying. The inlet air temperature of the spray drying process is 230°C to 260°C, such as 230°C, 235°C, 240°C, 245°C, 250°C, 255°C or 260°C; the outlet air temperature is 95°C to 120°C, such as 95°C, 100°C, 105°C, 110°C, 115°C or 120°C; the water content of the dried material is ≤4%, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%; the particles in the dried material have a spherical morphology, and the D50 particle size thereof is 20μm to 50μm, such as 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm.

[0090] Optionally, the D50 particle size of the crushed material is 1.0 μm to 1.8 μm, for example, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm or 1.8 μm.

[0091] Optionally, the sintering treatment includes the following steps: in a protective atmosphere, heating to 800°C to 900°C and keeping the temperature for 5h to 8h. The protective gas in the protective atmosphere includes nitrogen, helium, neon, argon or xenon, and nitrogen can be further selected; the sintering temperature can be 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C, and 800°C can be further selected; the holding time can be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, and 8h can be further selected.

[0092] Optionally, after the sintering process, a screening process is further included to remove large particle products. In a second aspect of the present application, a lithium iron phosphate material is provided, which is prepared by the preparation method of the lithium iron phosphate material as described above.

[0093] Optionally, the D50 particle size of the lithium iron phosphate material is 1 μm to 1.8 μm, for example, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm or 1.8 μm.

[0094] Optionally, the carbon content of the lithium iron phosphate material is 1.20% to 1.30%, for example, 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27%, 1.28%, 1.29% or 1.30%.

[0095] Optionally, the compaction density of the lithium iron phosphate material is ≥2.47g / cm 3 , for example 2.47 g / cm 3 , 2.48g / cm 3 , 2.50g / cm 3 , 2.52g / cm 3 , 2.54g / cm 3 , 2.56g / cm 3 , 2.58g / cm 3 or 2.60g / cm 3 .

[0096] Optionally, the specific surface area of ​​lithium iron phosphate is ≥ 13.07 m 2 / g, for example 13.07m 2 / g, 13.2m 2 / g, 13.3m 2 / g, 13.4m 2 / g, 13.5m 2 / g, 13.6m 2 / g, 13.7m 2 / g, 13.8m 2 / g or 14.0m 2 / g.

[0097] Optionally, the 0.1C discharge specific capacity of the lithium iron phosphate material is ≥158 mAh / g, for example, 158 mAh / g, 159 mAh / g, 160 mAh / g, 161 mAh / g, 162 mAh / g, 163 mAh / g, 164 mAh / g or 165 mAh / g.

[0098] Optionally, the 1C discharge specific capacity of the lithium iron phosphate material is ≥137 mAh / g, for example, 137 mAh / g, 138 mAh / g, 139 mAh / g, 140 mAh / g, 142 mAh / g, 144 mAh / g, 146 mAh / g or 148 mAh / g.

[0099] Optionally, the 1C / 0.1C ratio of the lithium iron phosphate material is ≥86.16%, for example, 86.16%, 86.2%, 86.4%, 86.6%, 86.8%, 87.0%, 87.2%, 87.4%, 87.6%, 87.8% or 88.0%.

[0100] In a third aspect of the present application, a positive electrode plate is provided, comprising the lithium iron phosphate material as described above.

[0101] Optionally, the positive electrode sheet includes a positive current collector and a positive active layer covering at least one surface of the positive current collector, and the positive active layer includes the lithium iron phosphate material as described above. The positive active layer covers at least one surface of the positive current collector, and may cover only one surface, or may cover two opposite surfaces at the same time, so as to form a structure in which the positive active layer, the positive current collector and the positive active layer are stacked in sequence.

[0102] Optionally, the positive electrode current collector includes a metal foil or a composite current collector. The metal foil may be aluminum foil; the composite current collector includes a polymer substrate and a metal layer formed on the polymer substrate, the polymer substrate may be made of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE), and the metal layer may be made of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.

[0103] Optionally, the positive electrode active layer includes a positive electrode material, a binder and a conductive agent, wherein the positive electrode material is used for lithium ion deintercalation, the binder is used to improve the bonding strength between the positive electrode active layer and the positive electrode current collector, and the conductive agent is used to improve the conductivity of the positive electrode active layer.

[0104] Optionally, the positive electrode material can be composed only of the lithium iron phosphate material as described above, or it can be composed of the lithium iron phosphate material as described above and other positive electrode materials, such as a combination of lithium iron phosphate material and nickel-cobalt-aluminum ternary material, a combination of lithium iron phosphate material and lithium manganese oxide material, or a combination of lithium iron phosphate material and lithium iron manganese phosphate material.

[0105] Optionally, in the positive electrode active layer, the mass ratio of the positive electrode material, the binder and the conductive agent is (80~95):(2~6):(2~6).

[0106] Optionally, the binder includes one or more of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE), and polyacrylic acid (PAA).

[0107] Optionally, the conductive agent includes one or more of conductive carbon, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers.

[0108] In a fourth aspect of the present application, a lithium-ion battery is provided, comprising the positive electrode plate as described above.

[0109] It can be understood that lithium-ion batteries include positive electrode sheets, negative electrode sheets, electrolytes and separators. During the charge and discharge cycle, active lithium ions are intercalated and deintercalated between the positive electrode sheets and the negative electrode sheets; the electrolyte conducts lithium ions between the positive electrode sheets and the negative electrode sheets; the separator is located between the positive electrode sheets and the negative electrode sheets to prevent short circuits while allowing active lithium ions to pass through.

[0110] Optionally, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer covering at least one surface of the negative electrode current collector. The negative electrode current collector includes a metal foil or a composite current collector. The metal foil in the negative electrode current collector can be copper foil. The composite current collector in the negative electrode current collector is basically the same as the composite current collector selected for the positive electrode current collector, and will not be described in detail.

[0111] Optionally, the negative electrode active layer includes a negative electrode material, a binder and a conductive agent. The negative electrode material includes one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material; the binder includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS); the conductive agent includes one or more of conductive carbon, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers.

[0112] It is understood that the electrolyte in a lithium-ion battery can be liquid, gel or all-solid.

[0113] Optionally, the electrolyte uses an electrolyte solution, which includes a lithium salt and an organic solvent. Among them, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate; the organic solvent includes one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0114] Optionally, the electrolyte further includes additives, such as negative electrode film-forming additives, positive electrode film-forming additives, additives for improving battery overcharge performance, additives for improving battery high or low temperature performance, etc.

[0115] Optionally, the material of the separator includes one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. It is understandable that the separator can be a porous separator with good chemical stability and mechanical stability; at the same time, the separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions.

[0116] It can be understood that the lithium-ion battery of the present application includes a battery cell form, a battery module form and a battery pack form. The shape of the lithium-ion battery can be cylindrical, square or other arbitrary shapes.

[0117] Optionally, the positive electrode sheet, the negative electrode sheet and the separator can be made into a battery cell through a winding process or a lamination process.

[0118] Optionally, the lithium-ion battery may include an outer package for encapsulating the above-mentioned battery cell and electrolyte. The outer package of the lithium-ion battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the lithium-ion battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate, etc.

[0119] Optionally, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more. The battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more.

[0120] Optionally, the battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices include, but are not limited to: mobile devices, such as mobile phones, tablet computers, and laptop computers; electric vehicles, such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.; electric trains; ships; satellites; and energy storage systems.

[0121] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0122] Example 1

[0123] Please refer to Table 1, the preparation method of the lithium iron phosphate material of this embodiment is as follows:

[0124] (1) An iron source, a phosphorus source, a lithium source, a carbon source and a dopant are uniformly mixed to obtain a mixture; a portion of the mixture is placed in a jet mill for pulverization to obtain a precursor A, and the remaining mixture is recorded as a precursor B.

[0125] Among them, the iron source and phosphorus source are iron phosphate, and the lithium source is lithium carbonate;

[0126] The molar ratio of iron to lithium (i.e., iron-lithium ratio) is 1:1.02;

[0127] The carbon source is glucose and PEG-2000 with a mass ratio of 2:1, and the molar ratio of carbon element in the carbon source to iron element in ferric phosphate is 7:100;

[0128] The dopant is titanium dioxide, and the molar ratio of titanium to iron in iron phosphate is 0.83:100;

[0129] The D50 particle size of precursor A is 1 μm, and the D50 particle size of precursor B is 8 μm;

[0130] The mass ratio of precursor A to precursor B is 8:2.

[0131] (2) Precursor A and precursor B were added into pure water at the same time to obtain a mixture with a solid content of 40%; the mixture was placed in a sand mill, stirred evenly with a stirring paddle, and sand-milled with a 0.3 mm zirconium ball to obtain a slurry with a D50 particle size of 600 nm.

[0132] (3) The slurry was transferred to a dispersion tank and spray-dried using a centrifugal spray dryer, with the inlet air temperature controlled at 255°C and the outlet air temperature controlled at 105°C, to obtain a dry material with spherical particles, a D50 particle size of 30 μm, and a water content of <4%.

[0133] (4) The dried material is added into a jet mill for pulverization, and the grading frequency is adjusted to obtain a pulverized material with a D50 particle size of 1.5 μm.

[0134] (5) The crushed material is transferred to a roller kiln, and sintered from room temperature to 800°C under nitrogen protection, and kept warm for 8 hours; after sintering, it is cooled with cooling water, then naturally cooled to room temperature, and sieved with a 200-mesh sieve to remove large particles of product, thereby obtaining a lithium iron phosphate material with a D50 particle size of 1.5 μm.

[0135] Embodiments 2 to 8

[0136] Embodiments 2 to 8 are substantially the same as Embodiment 1, except that:

[0137] Example 2: The mass ratio of precursor A to precursor B is 5:5.

[0138] Example 3: The mass ratio of precursor A to precursor B is 2:8.

[0139] Example 4: The D50 particle size of precursor A is 1 μm, and the D50 particle size of precursor B is 10 μm;

[0140] Example 5: The carbon source is selected from glucose and PVA in a mass ratio of 2:1.

[0141] Example 6: Vanadium pentoxide is selected as the dopant, and the molar ratio of vanadium element to iron element in iron phosphate is 0.83:100.

[0142] Example 7: The D50 particle size of the slurry obtained in step (2) is 900 nm.

[0143] Example 8: The sintering conditions of step (5) are: keeping warm at 900°C for 5 hours.

[0144] Comparative Examples 1 to 3

[0145] Comparative Examples 1 to 3 are substantially the same as Example 1, except that:

[0146] Comparative Example 1: In step (1), part of the mixed material was not subjected to air flow milling, that is, the mass ratio of precursor A to precursor B was 0:10.

[0147] Comparative Example 2: In step (1), all the mixed materials were subjected to air flow pulverization, that is, the mass ratio of precursor A to precursor B was 10:0.

[0148] Comparative Example 3: In step (2), the precursor A, precursor B and pure water are mixed and then directly spray-dried without nano-processing.

[0149] Test Case

[0150] The lithium iron phosphate materials of each embodiment and each comparative example were tested as follows:

[0151] (1) Morphology test: The powder material sample was fixed on the sample stage with conductive glue, and the sample morphology was observed in a scanning electron microscope (SEM). The D50 particle size was measured using Nano Measurer software. The results are shown in Table 2 and Figure 1~Figure 4 .in, Figure 2 is a SEM image of the lithium iron phosphate material of Example 1, Figure 3 is a SEM image of the lithium iron phosphate material of Example 2, Figure 4 is a SEM image of the lithium iron phosphate material of Example 3, Figure 5 This is the SEM image of the lithium iron phosphate material of Comparative Example 1.

[0152] (2) Compacted density: Referring to GB / T 7314-2005 Metal Materials Room Temperature Compression Test Method, the compacted density of lithium iron phosphate material was measured using an electronic compression testing machine. The results are shown in Table 2.

[0153] (3) Specific surface area: The specific surface area analyzer was used. The adsorption gas was nitrogen and the degassing conditions were 320 °C and 1 h. The results are shown in Table 2.

[0154] (4) Carbon content: The carbon content of the lithium iron phosphate material was tested using an infrared carbon-sulfur analyzer. The results are shown in Table 2.

[0155] (5) Battery performance: Lithium iron phosphate material was mixed with binder PVDF and conductive agent SP in a mass ratio of 90:5:5, and NMP was used as solvent. The mixture was stirred evenly to obtain positive electrode slurry. The positive electrode slurry was coated on aluminum foil, and after drying and rolling, discs were cut out to serve as positive electrode sheets. Lithium sheets were used as negative electrode sheets. The lithium salt in the electrolyte was 1 mol / L LiPF6, and the solvent was a mixture of dimethyl carbonate (DMC) and ethylene carbonate (EC), with a volume ratio of DMC to EC of 1:1. The cells were assembled into button batteries, and the capacity was tested using a battery performance test system of model CT3002A produced by Wuhan Blue Electric Electronic Technology Co., Ltd. The test temperature was 25°C, the voltage range was 2~4.5V, and the rate range was 0.1C~3C. The results are shown in Table 2.

[0156] Depend on Figure 1~Figure 4 As shown in Table 2, Examples 1 to 8 use two precursors with different chemical reaction activities to control the growth rate of lithium iron phosphate grains, and combine element doping, carbon coating, nano-sizing, spray drying, air flow milling and high-temperature sintering to make the lithium iron phosphate material show the effect of large and small particle grading, and its compacted density reaches 2.47g / cm 3 The 0.1C discharge capacity reaches more than 158mAh / g, the 1C discharge capacity reaches more than 137mAh / g, and the 1C / 0.1C rate reaches more than 86.16%.

[0157] In Comparative Example 1, part of the mixture was not subjected to airflow pulverization treatment. There was no difference in the chemical reaction activity between the precursors, and the growth rate of the grains was basically the same, resulting in the lithium iron phosphate material being unable to form a large and small particle gradation effect, and the D50 particle size of its secondary particles was small, and the compaction density and rate performance were reduced. In Comparative Example 2, all the mixtures were subjected to airflow pulverization treatment. The precursors all had high chemical reaction activity and small particle size, and the grain growth rate was fast, resulting in reduced compaction density, discharge specific capacity and rate performance. In Comparative Example 3, there was no nano-treatment, and the slurry had a high particle size and poor dispersibility, which was not conducive to the growth of grains. Therefore, the compaction density, discharge specific capacity and rate performance of the product were also significantly reduced.

[0158] In addition, in the preparation process of Examples 1 to 8, there is no need to add additional large particles or small particles for grading, and there is no need to feed in batches, sinter in multiple stages or perform long-term heat preservation treatment. The steps are simple and controllable, the stability between batches is good, and mass production can be achieved.

[0159] Table 1. Relevant parameters of the preparation process of lithium iron phosphate materials

[0160]

[0161] Table 2. Performance comparison of lithium iron phosphate materials

[0162]

[0163] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0164] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a lithium iron phosphate material, characterized in that: The following steps are involved: A mixture containing an iron source, a phosphorus source, a lithium source, a carbon source and a dopant is prepared, and a part of the mixture is subjected to a first airflow pulverization treatment to obtain a precursor A, and the remaining mixture is recorded as a precursor B; The precursor A, the precursor B and a solvent are mixed and nano-processed to obtain a slurry; The slurry is subjected to a drying process, a second air flow pulverization process and a sintering process to obtain the lithium iron phosphate material.

2. The method for preparing the lithium iron phosphate material according to claim 1, characterized in that: The mass ratio of the precursor A to the precursor B is (1~9):(1~9).

3. The method for preparing the lithium iron phosphate material according to claim 2, characterized in that: The D50 particle size of the precursor A is 1 μm to 2 μm, and the D50 particle size of the precursor B is 8 μm to 10 μm.

4. The method for preparing the lithium iron phosphate material according to any one of claims 1 to 3, characterized in that: One or more of the following conditions are met: (1) The molar ratio of the iron element in the iron source, the phosphorus element in the phosphorus source, and the lithium element in the lithium source is 1:(0.95-1.05):(1.01-1.05); (2) The iron source includes one or more of ferric phosphate, ferric nitrate, ferric sulfate, ferric chloride, ferrous oxalate, ferrous acetate, ferrous sulfate, ferrous chloride and ferrous oxide; (3) The phosphorus source includes one or more of ferric phosphate, phosphoric acid, dihydrogen phosphate and monohydrogen phosphate; (4) The lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium chloride, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium oxalate and lithium acetate; (5) The molar ratio of the carbon element in the carbon source, the doping element in the dopant, and the iron element in the iron source is (7-10):(0-1.16):100; (6) The carbon source includes one or more of glucose, sucrose, fructose, starch, cellulose, citric acid, polyethylene glycol and polyvinyl alcohol; (7) The doping element in the dopant includes one or more of titanium, magnesium, aluminum, vanadium, niobium, zirconium, lanthanum and yttrium.

5. The method for preparing the lithium iron phosphate material according to claim 4, characterized in that: The drying process comprises spray drying process; The inlet air temperature of the spray drying process is 230°C to 260°C, and the outlet air temperature is 95°C to 120°C.

6. The method for preparing the lithium iron phosphate material according to claim 5, characterized in that: The sintering process comprises the following steps: In a protective atmosphere, raise the temperature to 800℃~900℃ and keep it warm for 5h~8h.

7. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material is prepared by the preparation method of the lithium iron phosphate material according to any one of claims 1 to 6.

8. The lithium iron phosphate material according to claim 7, characterized in that: One or more of the following conditions are met: (1) The carbon content of the lithium iron phosphate material is 1.20% to 1.30%; (2) The compaction density of the lithium iron phosphate material is ≥ 2.47 g / cm 3 ; (3) The 1C / 0.1C ratio of the lithium iron phosphate material is ≥86.16%.

9. A positive electrode sheet, characterized in that: Comprising the lithium iron phosphate material as described in claim 7 or 8.

10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.